ChemInform Abstract: A New MCM‐41 Supported HPF6 Catalyst for the Library Synthesis of Highly Substituted 1, 4‐Diyhdropyridines and Oxidation to Pyridines: Report of One‐Dimensional Packing Towards LMSOMs and Studies on Their Photophysical Properties. Issue 44 (14th October 2013) - Ray, Suman; Brown, Mike; Bhaumik, Asim; Dutta, Arghya; Mukhopadhyay, Chhanda
Abstract A series of substituted 1, 4‐dihydropyridines (IV) is readily prepared by a multi‐component condensation of diketones (I) with ketones (II), aryl aldehydes (III), and ammonium carbonate using MCM‐41 supported HPF6 as a novel heterogeneous catalyst.